(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
In the process of introducing our students of junior school age to the world and nature around us, the main attention is paid to environmental problems. In this, the influence of man on nature, the interaction and connection of plants with plants, plants with animals, and animals with animals are studied. This article is devoted to the effectiveness of using specific forms, methods and tools in the development of natural knowledge comprehension skills.